2019
DOI: 10.34117/bjdv5n6-134
|View full text |Cite
|
Sign up to set email alerts
|

Infecção por Aelurostrongylus abstrusus em felino-Relato de caso

Abstract: RESUMOA aelurostrongilose em gatos é causada pelo nematóide Aelurostrongylus abstrusus, um parasita cosmopolita, relativamente pouco diagnosticado. Este parasita é encontrado nos brônquios e artérias pulmonares do hospedeiro e a infecção em indivíduos saudáveis é subclínica podendo chegar a uma broncopneumonia intersticial, dispneia e desconforto respiratório em infecções maciças. No presente artigo relata-se um caso de aelurostrongilose em um gato doméstico apático e anoréxico, sem sinais respiratórios. Outro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Previous studies from South America reported prevalence rates of 0.21% in Colombia, 8.6% in Uruguay, from 2.6 to 35.3% in Argentina and from 1.3 to 29.5% in Brazil [ 24 ]. Literature data on the occurrence of A. abstrusus in Brazil from the last two decades describe infection rates of 1.37–18% [ 27 , 39 , 40 , 41 , 42 , 43 , 44 ], thus the herein results are in line with these lower range values. However, it should be taken into account that a relatively small number of cats has been examined in the present study, and this is not representative of the territorial epizootiological scenario.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies from South America reported prevalence rates of 0.21% in Colombia, 8.6% in Uruguay, from 2.6 to 35.3% in Argentina and from 1.3 to 29.5% in Brazil [ 24 ]. Literature data on the occurrence of A. abstrusus in Brazil from the last two decades describe infection rates of 1.37–18% [ 27 , 39 , 40 , 41 , 42 , 43 , 44 ], thus the herein results are in line with these lower range values. However, it should be taken into account that a relatively small number of cats has been examined in the present study, and this is not representative of the territorial epizootiological scenario.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of A. abstrusus in felines varies widely among countries and regions worldwide, with the disease considered endemic in the European continent (Knaus et al 2011; Echeverry et al 2012; Barutzki and Schaper 2013; Olsen et al 2015). In Brazil, several states have reported this parasite, including Minas Gerais (Mundim et al 2004), Mato Grosso (Ramos et al 2013), Goiás (Campos et al 1974), Rio de Janeiro (Scofield et al 2005; Ferreira et al 2007), São Paulo (Fenerich et al 1975; Matsui et al 2018), and Rio Grande do Sul (Ehlers et al 2013; Rigão et al 2019; Ferraz et al 2020). Since this lungworm was confirmed as an important cause of death in cats in our region (Pereira et al 2017), we were motivated to study its occurrence among our patients presented with cough or evidence of bronchopulmonary disease on radiographic evaluation.…”
Section: Discussionmentioning
confidence: 99%